(untitled) (Annals of Bangladesh Agriculture, 2023)
Moringa, a multi-purpose and highly valued tree that possesses pharmacological properties which are widely used in medicine to treat a variety of diseases. The current study aimed to collect superior accessions from Bangladesh’s key moringa-growing regions through in-situ evaluation and document them by using morphological (qualitative and quantitative) traits and nutritional value in order to conserve the best indigenous landraces. Four major moringa growing regions in Bangladesh were selected namely, Chapai Nawabganj, Rangpur, Lalmonirhat and Rangamati. Twelve moringa accessions were collected during 2019-2020 based on the farmer’s preferences and morphological traits. The information on 35 quantitative and 16 qualitative aspects was analyzed using the International Plant Genetic Resource Institute (IPGRI), 2007 technique. The results demonstrated that flowering and fruiting occurred yearly in seasonal accession and three times per year in year-round accession. The flowers ranged in color from white to cream and year-round accession s MO8 and MO10 had corollas that were white with red spots. The seasonal accession’s MO1 exhibited the highest pods (97.22 g) weight, while the year-round accession’s MO12 had the lowest (45.16 g) pod weight. Leaves contained more than two times higher protein (23–34%) compared to pods (11–18%). As with nutrients, leaves had much higher levels of Ca and Fe (2137 to 3633 ppm and 252 to 424 ppm, respectively) than pods (2013 to 2875 ppm and 54- 69 ppm, respectively). Overall, the findings imply that there were numerous changes in the most important qualitative and quantitative traits as well as nutrients available in different parts of moringa. The information and analysis from these investigations could contribute to the genetic development of the species. Ann. Bangladesh Agric. (2022) 26 (2) : 33-49